Development of a lambda Red based system for gene deletion in Chlamydia. - Yibing Wang; Robert Suchland; Amy Hua; Steven Carrell; Daniel Rockey; Kevin Hybiske (PLoS ONE)
The ability to efficiently target loci in the Chlamydia trachomatis genome for deletion remains a desirable goal in the field and new strategies need to be developed and refined. Here we describe the development and application of a lambda red recombineering system for Chlamydia. Using a non-replicative plasmid encoding key lambda Red components and targeting sequences, we demonstrate the efficient deletion of numerous gene targets in the model chlamydial strains C. trachomatis L2/434 and C. muridarum. For initial development of the system, we targeted the incA gene of C. trachomatis for deletion. Deletion mutants containing a chloramphenicol resistance marker were recovered within 3 rounds of selection, or 2 rounds of passaging, in McCoy cells and the resulting clones (CTΔincA) were verified by PCR-based genotyping and whole genome sequencing. Phenotypic assessment of host cells infected with CTΔincA was performed by immunofluorescence microscopy and confirmed the lack of IncA expression and the uniform presence of nonfusogenic vacuoles (inclusions) across CTΔincA-infected monolayers. To explore the utility of this system, we deleted 5 additional candidate virulence factors in C. trachomatis and C. muridarum, including deletions of single and multiple genes. We expect lambda Red recombineering to offer a powerful new strategy for making gene deletion and/or replacement mutants in Chlamydia.